Hubungan Peran Tim Pencegahan dan Pengendalian Infeksi (Tim PPI) dan Fasilitas Cuci Tangan dengan Kepatuhan Cuci Tangan Perawat - Sulisno, Madya; Nurmalia, Devi; Warsito, Bambang Edi; Jannah, Ayu Miftahul; Ulliya, Sarah; Santoso, Agus; Ardani, Muhammad Hasib (Holistic Nursing and Health Science, 2022)
Introduction: Health care associated infections (HCAIs) are infections that patients get during hospitalization. The most effective prevention of HCAIs is hand washing. Hand washing compliance behavior is still quite low. Nurses' hand washing compliance needs to be improved by optimizing the role of the Infection Prevention and Control Team (PPI team) and adequate hand washing facilities. Research related to the role of the PPI team and existing hand washing facilities still shows mixed results, therefore it is interesting to study.Methods: This study used a descriptive correlational design that aims to determine the relationship between the role of the PPI team and hand washing facilities with nurses' hand washing compliance. The research sample consisted of 204 nurses who were taken at simple random, data collection using questionnaires and observation sheets. The questionnaire consisted of 10 questions for the role of the PPI Team variable and 5 questions for the variable hand washing facilities and 11 statements for observing nurse handwashing compliance.Results: The results showed that nurses who obeyed hand washing were 88% and did not comply with 12%, the role of the PPI team performed well at 97.5% and not good 2.5% and the availability of hand washing facilities were considered good at 97.5% and not good 2,5%. The results of the Chi-Square test showed that there was a significant relationship between the role of the PPI team and nurses' hand washing compliance (P = 0.0001) and there was a significant relationship between the completeness of hand washing facilities and nurses' hand washing compliance (P = 0.007).Conclusion: Based on the results of this study, nurses are expected to be able to maintain and improve hand washing and transform these good habits for other health teams, patients, families, and visitors. In addition, the PPI team must continue to work optimally and the hospital can provide complete hand washing facilities